North Atlantic Ocean-atmosphere interaction on intraseasonal time scales - Ciasto, Laura M., author (Colorado State University. Libraries, 2004)
A substantial fraction of midlatitude sea surface temperature (SST) variability on time scales ranging from months to years can be interpreted as the passive thermodynamic response of the ocean mixed layer to stochastic atmospheric forcing. Subsequently, the dominant structures of monthly and seasonal mean Northern Hemisphere SST variability owe their existence to variations in the extratropical atmosphere. To what extent midlatitude SST variability, in tum, gives rise to anomalies in the dominant structures of extratropical atmospheric variability remains unclear. Presumably, if the extratropical atmosphere exhibits a deep and statistically significant response to midlatitude SST anomalies, the dynamics of the response should occur on time scales shorter than the monthly and seasonal mean data used in most observational analyses of midlatitude atmosphere-ocean interaction. The motivation of the thesis is to investigate the interaction between North Atlantic SST variability and the extratropical atmospheric circulation on intraseasonal time scales. First, the climatology of the North Atlantic SST field and the overlying atmospheric circulation is described. The largest variance in intraseasonal and seasonal mean SST anomalies is located within a zone of enhanced SST gradients in the Gulf Stream extension. The region of maximum SST variance also underlies a region of marked wintertime cyclogenesis over the western edge of the North Atlantic storm track. Patterns of North Atlantic weekly SST variability are further investigated using Empirical Orthogonal Function (EOF) analysis. EOFs of both weekly summertime and wintertime SST anomalies reflect a mix of two patterns, variability in the Gulf Stream extension region and a meridionally banded structure of SST anomalies commonly referred to as the tripole. These patterns are most clearly evident in EOFs based on intraseasonal wintertime SST anomalies. Wintertime atmosphere-ocean interaction on intraseasonal time scales is then examined using lagged correlation/regression analysis. The results show that the tripole and variability in the Gulf Stream extension region emerge not only as the leading EOFs of intraseasonal wintertime SST variability but also in association with the leading pattern of Northern Hemisphere atmospheric variability, referred to as the Northern Annular Mode (NAM). Consistent with previous results, the strongest correlations between midlatitude SSTs and the NAM occur when variations in the NAM lead the tripole by ~2 weeks. However, the present results also show a coherent and statistically significant pattern of SST anomalies over the Gulf Stream extension region that precedes changes in the NAM by ~2 weeks.
Summer 2004.
Also issued as author's thesis (M.S.) -- Colorado State University, 2004.
Keywords: Ocean-atmosphere interaction -- North Atlantic Ocean